Efectivizar las medidas socio-educativas en el código de la niñez y adolescencia, con la finalidad de reducir el índice de reincidencia de adolescentes infractores en delitos sancionados con privación de libertad y necesidad de reformar - Pérez Morales, Marco Antonio (2015)
From before the current Constitution of the Republic of the Ecuador enters in validity approved by means of referendum and published in the R. O. Number 449 of October 20 2008, the children, girls and adolescents considered as weak groups and at the moment as groups of high-priority attention, they are subject of several inherent rights to its age; to their physical, psychic and emotional development; to be integrated in cultural, educational, sport or recreational activities; as well as the duty of the State of eradicating the infantile work, to protect the adolescents of the labor, sexual exploitation or of any other nature. In the Art. 175 of the Constitution of the Republic settle down that an administration of specialized justice exists for the concerning matters to the children and adolescents, in a first aspect of defense of the inherent rights to its age, and in a second place in the judgment of adolescent lawbreakers. Reason why it has been excluded of the ordinary penal jurisdiction the judgment of the adolescent lawbreakers to who the Judges of the Family, Woman, Childhood and Adolescence and of being demonstrated their responsibility in the commission of an infraction established in the penal law, they are imposed those denominated partner-educational measures that have for object the reinstatement from the adolescent to the family breast and to achieve a behavior correction so much in the social environment as the repair of the caused damage, all this in function of the principle of the boy's superior interest. The current partner-educational measures settled down in the Organic Code of the Childhood and Adolescence, are applicable for the commitment of breaches, crimes sanctioned with prison and of the crimes sanctioned with reclusion, understanding this last class to those of special bigger reclusion. In spite of the existence of measures of preventive character and the adolescents' resocializer that have infringed the legal norms, and likewise they have incurred in the penal norms, it is of imperious necessity to establish reformations to the Code of the Childhood and Adolescence that effecting the partner-educational measures, in order to reducing the index of adolescent transgressors' reincidence that they comment crimes sanctioned with reclusion or that they cause great social shock, such as the homicide, murder, plagiarism (people's kidnapping), violation among others. Mainly because the delinquency leans on in the legal deficiencies to take out profit, this way the use of adolescents for the mafias or criminal organizations goes in increase, because they know with all certainty that you cannot apply the penal sanction but rather they will apply a light measure, for it is necessary effecting the partner-educational measures, mainly with a surveillance of the authority that knows of the infraction made by the adolescent, so that it is mitigated of root the reincidence possibility, as well as that takes charge the Judge of the Family, Woman, Childhood and Adolescence of remitting the district attorney the names of the criminals that are using adolescents to make serious infractions.